Peculiarities of contractual liability under martial law - Stefanchuk, Mykola (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article analyzes the issue of the peculiarities of contractual liability in the conditions of martial law. The normative and legal regulation of circumstances of force majeure in the legislation of Ukraine and foreign countries is studied. The category of force majeure circumstances was studied and their characteristics were determined, among which the lack of control, exclusivity, unpredictability and inevitability stand out. The question of formulating the force majeure condition in national and international contracts is analyzed. It is substantiated that despite the use of the concepts of “force majeure” and “circumstances of force majeure” as synonyms in the civil legislation of Ukraine, it is necessary to separate them.The concept of martial law varies among different countries, and the specific rules and regulations regarding contractual liability under martial law can also vary depending on the jurisdiction. However, in general, martial law is often declared during times of emergency or crisis, such as war, natural disasters, or civil unrest, and it grants the military or other government authority’s greater powers to maintain law and order.Under martial law, contractual liability may be affected in several ways. For example, contracts may be suspended or terminated if they are deemed to be incompatible with the goals or objectives of the martial law regime. This may include contracts that involve sensitive or strategic assets, or contracts with foreign entities that may be seen as a threat to national security.In some cases, the government may also be granted the power to modify or renegotiate existing contracts in order to better serve the needs of the martial law regime. This may include changes to pricing, delivery timelines, or other terms of the contract.It is important to note that under martial law, there may be limitations on the ability of parties to pursue legal action related to contractual liability. For example, courts may be closed or their jurisdiction may be limited, and the military or other government authorities may be granted immunity from legal action related to their actions taken under martial law.Overall, contractual liability under martial law can be complex and may vary depending on the specific circumstances and jurisdiction. It is important for individuals and businesses to consult with legal professionals to understand their rights and obligations in these situations.